Report on activities in favour of small member states during the biennium 1998-1999 (UNESCO [Geneva]CH, 1999)
Focuses on various activities in small states viz. education; sciences in the service of development; cultural development; communication; information and informatics; and also, transdisciplinary projects.
Keywords: SMALL STATES